Pakistan Society of Development Economists: Secretary's Report (The Pakistan Development Review, 1985)
Aims and Objectives The Society, based in the Pakistan Institute of Development Economics is registered under the Societies Registration Act, 1860. This registration ensures that the society maintains its autonomy and grows in its own right. It is a unique institution. It is an autonomous body with a constitution and bye-laws that govern its functioning. Its decisions are taken independently without any interference from any quarter but with active consultation among its members. The Society is not a trade union of development economists. ]t only provides an academic forum for contact between economists associated with the Institute and those outside the Institute. The Society aims at achieving professional excellence and at the creation and dissemination of knowledge in the field of development economics. According to its charter, the Society encourages perfect freedom of economic discussion. The Society does not take any partisan attitude nor commits itself to any position on practical economic issues.